The Summer School of the German Society for Orthopaedics and Traumatology - A Success Story - Merschin, D.; Mutschler, M.; Stange, R.; Kopschina, C.; Schuettrumpf, P.; Doepfer, A. K.; Achatz, G.; Niethard, M.; Hoffmann, R.; Kladny, B.; Muenzberg, M.; Perl, Mario (Zeitschrift für Orthopädie und Unfallchirurgie, 2016)
Background: It has been known for several years that orthopaedic and trauma clinics suffer from a shortage of young people, due to the substantial loss in attractiveness. The Youth Forum OU has been addressing this problem for many years, by initiating many projects such as the Summer School to counteract this trend. The purpose of this research is to evaluate the success of Summer Schools since 2009.Methods: The Youth Forum OU performed a survey in December 2014 to answer the research question on the basis of an internet-based poll of the student participants in all Summer Schools between 2009 and 2014. Following data cleansing, 121 students and former students were included in the survey.Results: Seventy-two completed questionnaires were collected and included in the evaluation. The survey included 40% of Summer School participants, with a mean age of 27.3 years (SD +/- 2.95); 50% were female. Participation in the Summer School helped 50% of the respondents to decide to start advanced study in orthopaedics and/or traumatology (OU). One third of these Summer School participants had already finished a university degree; 100% are now residents in orthopaedics and/or traumatology. Regardless of prior plans, 87.2% of participants are now residents in OU. Thirty-three are still students: 78.8% have already decided to work in OU. The survey also served to identify the factors positively and negatively associated with OU. Unfavourable factors included the reputation of OU, and the difficulty of reconciling family and work. Favourable factors included surgical work and personal experience during university studies.Discussion: The aim of this study was to evaluate whether the efforts of the Youth Forum OU, the German Society for Orthopaedics and Traumatology (DGOU) and the local hospitals lead to increased interest in OU. The answer to this question is positive. This is particularly true for those students who did not plan to become an orthopaedic or trauma surgeon before participating in a Summer School. In conclusion, the efforts to recruit residents for OU by using Summer Schools were successful. Moreover, this research offers approaches to counteract the loss of attractiveness of OU.
Keywords: promotion of the young; residency; shortage of residents; youth forum